Examining the Relationship between Oil Prices and Stock Returns: Evidence from OECD Countries - Havane Tembelo; Mustafa Ozyesil (International Journal of Energy Economics and Policy)
This study uses data from the OECD countries to investigate the relationship between stock returns and oil prices. The study uses daily closing values for analysis and covers the years 2000 - 2022. Oil prices are taken as the independent variable and stock returns as the dependent variable using the panel data analysis. The analysis includes intermediary factors as GDP and inflation. The research begins with a unit root test, followed by a panel co-integration test. Finally, the panel causality test and panel regression results are interpreted. This study primarily aims to explore the effect of oil price volatility on stock returns. Results show a statistically significant positive association between stock returns and oil prices. These findings highlight the importance of oil prices as a determinant of stock returns in the financial markets and provide investors, financial institutions and policymakers valuable insights.